2020
DOI: 10.1093/jamia/ocaa167
|View full text |Cite
|
Sign up to set email alerts
|

User reactions to COVID-19 screening chatbots from reputable providers

Abstract: Abstract Objective The objective was to understand how people respond to COVID-19 screening chatbots. Materials and Methods We conducted an online experiment with 371 participants who viewed a COVID-19 screening session between a hotline agent (chatbot or human) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 20 publications
0
53
0
1
Order By: Relevance
“…Additionally, our review showed that health chatbots were used in multiple domains. The most prevalent domains were preventive care and risk communication (n=3) ( 3 , 9 , 12 ), public health surveillance by health officials (n=2) ( 2 , 10 ), Telehealth (n=2) ( 1 , 11 ), workplace health and safety (n=1) ( 13 ), and care of the elderly (n=1) ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, our review showed that health chatbots were used in multiple domains. The most prevalent domains were preventive care and risk communication (n=3) ( 3 , 9 , 12 ), public health surveillance by health officials (n=2) ( 2 , 10 ), Telehealth (n=2) ( 1 , 11 ), workplace health and safety (n=1) ( 13 ), and care of the elderly (n=1) ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, an application with a chatbot was developed to record health factors such as nutrition, physical activity, etc. during mandated self-isolation periods ( 9 , 10 , 12 , 14 ). Health chatbots were also used for tracking mood status to mitigate the psychological effects of COVID-19 such as anxiety, distress, and depression that could increase due to self-isolation, fear of becoming infected with the Coronavirus, or the stigma of contracting COVID-19 ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was done with 371 individuals that participated in a COVID-19 screening session and concluded that the primary factor that drove the user's decision was whether they trust the capability of the chatbot or not. Overall, the chatbot providing high-quality service is critical [97]. As the COVID-19 pandemic continues, the mental health of both the infected and noninfected is an important concern.…”
Section: Emergency Response and Covid-19mentioning
confidence: 99%